Optimizing Marketing In The Digital Era With A Digitalization Marketing Seminar To Advance Umkm In Pidodowetan Village - Agil Catur Maylani; Meli Apriliyani; Nok Vivi Fadillah; Maelani Afwaja; Fenny Bintarawati (Universitas Palangka Raya, 2024)
This research examines the use of social media to increase the attractiveness and sales of MSME products in Pidodowetan Village. Through a marketing digitalization seminar held on 8 August 2024 at the Pidodowetan Village Hall, MSME players were provided with knowledge and practical skills on digital marketing. The seminar covered materials on product branding, business management, and marketing strategies with a focus on the use of social media such as Instagram, Facebook, and WhatsApp. The results showed that the seminar was highly beneficial to the participants, with a high level of enthusiasm evident from active participation in the discussions. The program is designed to provide long-term impact through continued coaching and community support, aimed at driving local economic growth and creating a new generation of entrepreneurs who are competitive in the digital age.